Searching on Campus? Marriage Market Effects of the Student Gender Composition - Nico Pestel (Institute of Labor Economics (IZA), 2017)
This paper studies marriage market effects of the student gender composition for university graduates using German Microcensus data and aggregate information on the student sex ratio by field of study for 41 different fields from 1977 to 2011. Experiencing a higher own-gender share of students during university education reduces overall marriage market opportunities for women but not for men. Moreover, when students of the own gender are relatively abundant, the probability of having a partner from the same field decreases for women, while men are more likely to marry down with respect to educational status.
Keywords: D10; I23; I24; J12; 330; marriage markets; sex ratio; higher education; Germany